Significance of the principle of equal treatment of men and women in European union - Rajić Ćalić, Jovana (Glasnik Advokatske komore Vojvodine, 2023)
The issue of equal treatment of men and women is an inexhaustible topic for research, and as the problem of discrimination based on gender is closely related to the establishment of equal treatment, the research of this topic should be started from a supranational level, such as the legal system in the European Union. The emergence and development of the principle of equal treatment within the community of European states proceeded gradually, leaving room for additional improvements. The normative framework that was set, however, was not accompanied by practical changes in providing equal opportunities for women in employment and at work, and scientists are still dealing with the phenomenon of the wage gap, job segregation, the glass ceiling and the problem of harmonizing family and professional life, as a consequence unequal position of men and women in society. The paper examines the origin and development of the principle of equal treatment within the European Union, with the initial hypothesis that even the current normative framework is unable to prevent the consequences of discrimination based on gender that exist in practice.